Reforming economic governance in the Eurozone: Shifting spending instead of expanding debt margins - Clemens Fuest (CESifo GmbH, 2022)
In February 2020, the European Commission announced that it would present a plan for reforming the economic governance of the Eurozone, including the rules for public debt. The project was postponed by the outbreak of the corona pandemic, but now the reform is to come. There is a widespread demand to expand debt leeway, for example for climate protection spending. In view of the already very high national debt and rising inflation, this is the wrong way to go. Fiscal policy coordination should focus more on expenditure reallocations and thus on improving the quality, not the quantity of public spending. What is needed is a modified handling of the existing rules, not a change in the rules themselves.
Keywords: 330; EU-Wirtschaftspolitik; Governance-Ansatz; Europäische Finanzpolitik; Öffentliche Schulden; Eurozone